Desain Pembangkit Listrik Tenaga Surya (PLTS) Terapung pada Regulating Pond Aplikasi pada PLTA Renun UPDK Pandan PLN Kitsbu - Mochtar, Gatot; Hardi, Surya; Rohana, Rohana (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2023)
The less fossil fuel reserves in the world, especially Indonesia and environmental problems in the global sector caused by oil and gas exploration and mining, then alternative energy sources to replace fossil fuels or better known as renewable energy need to be developed. The Renun Hydroelectric Power Plant (PLTA) in North Sumatra has a water reservoir or so-called Regulating Pond with an area of ​​11.42 ha, the size of the Regulating Pond which is quite large is very appropriate if it is used for a Solar Power Plant (PLTS) because there is no land acquisition , and the Regulating Pond is more stable, there are no rising and falling contours. The solar panels used in floating solar panels on the regulating pound are 20,441 Polycristaline solar panels, 300 Wp power type Blue Sun Solar Energi BSM270-300P-60 (300W), the power generated is 6,123,300 Wp (6,123.3 kWp) or 6, 12 MWp. The batteries in PLTS consist of 275 series and 3.5 parallel and the total battery required is 1,100 JYC Batteries, OPzV3000 type batteries, and 9 inverters of the ABB brand PVI 500 TL CN with a power of 560 kW and a voltage of 360 V. The potential obtained from the PLTS planning in Regulating Pound for North Renun Hydroelectric Power Plant using Helioscope software simulation is 489,659 kWh/month.